AMLODIPINE ADVANTAGES IN ARTERIAL HYPERTENSION THERAPY - V. M. Tsareva; N. J. Hozjainova; M. S. Bezaltynnyh; T. V. Brook; N. A. Borohova; I. E. Koltunov; N. M. Ahmedzhanov (Рациональная фармакотерапия в кардиологии)
Aim. To study effects of calcium channel blocker, amlodipine on indices of ambulatory blood pressure monitoring (ABPM), heart rate variability, corrected QT-interval and its dispersion, structural and functional heart indices, microcirculation in patients with arterial hypertension (HT).Material and methods. 48 patients with HT of 1-2 stages were involved in the study. After 2 week wash-out period amlodipine (5-10 mg/day) therapy was started. ABPM, 24 hour electrocardiogram monitoring, echocardiography, laser Doppler flowmetry was performed initially and in 24 weeks of therapy.Results. Amlodipine therapy increased microcirculation efficacy, reduced repolarization nonhomogeneity, contributed to myocardial electrophysiological stability. Besides it improved structural and functional heart indices, decreased systolic and diastolic blood pressure (BP), reduced indices of BP load during a day.Conclusion. Amlodipine is effective antihypertensive medicine, having prominent cardio- and vasoprotective effects and good tolerability.